PENGARUH PENDIDIKAN DAN PELATIHAN, SUPERVISI, DAN KOMPETENSI PEDAGOGIK TERHADAP KOMITMEN PROFESI PADA GURU SMP NEGERI DI KABUPATEN SAROLANGUN PROVINSI JAMBI - Nurrahmi Lasahido; Lahmuddin Lubis; Candra Wijaya (Sekolah Tinggi Agama Islam Al Hidayah, 2015)
This research was aimed to determine the effect of education and training, supervision, and pedagogic competence of the commitment of teacher profession. This quantitative research using a survey methods and techniques of path analysis. The population was in junior high school teacher Sarolangun by the number of samples 247 respondents selected by proportional sampling The results of data analysis showed that (1) the education and training of a positive direct impact against teachers' commitment of to the profession, (2) the supervision of a positive direct impact against the commitment of the teacher profession, (3) pedagogic competence positive direct impact against the commitment of the teacher profession, (4) education and training direct positif effect against pedagogical, (5) supervision of the principal positive direct impact against pedagogic competencies. There is should be an effort to improve education and training based on the needs of teachers and pro-actively supervise principals in improving the profession of commitment. Kata kunci: pendidikan dan latihan, supervisi, kompetensi paedagogik, komitmen profesi guru